Role of reduced glutathione in Zn and Cd hyperaccumulation in Sedum alfredii H - CHAO Yue-en; ZHANG Min; LU Ling-li; FENG Ying; YANG Xiao-e (浙江大学学报. 农业与生命科学版, 2007)
Hyperaccumulating ecotype of Sedum alfredii H. was treated with 1000 μmol·L-1 Zn(NO3)2 or 200 μmol·L-1 CdCl2 for 25 days. Zn and Cd concentrations in plants, total sulphur (S) and reduced glutathione (GSH) in shoots, were detected every 5 days after treatment. Effects of S on Zn/Cd accumulation in Sedum alfredii H. were also investigated. The results indicate that Zn/Cd concentration in shoots of Sedum alfredii H. increased linearly within 15 days and after that increasing rate was declined considerably. Concentrations of total S and GSH in shoots were also increased within 15 days, and then decreased. Zn concentration in roots was found to be positively correlated with total S or GSH concentration in shoots, however, there is no such relationship with accumulation of Cd in the presence of S and GSH. These results suggest that SH-containing ligands is not the main chelator of Zn/Cd in the hyperaccumulating ecotype of Sedum alfredii H. GSH probably plays an important role in the detoxification of dissociated zinc/cadmium, while increasing S supplying level could increase zinc and cadmium accumulation of Sedum alfredii H. significantly.